Multilingualism and Language Contact in Maithili: Trends, Traits and Impact in Sociolinguistic Spaces - Gautam, Bhim Lal; Poudel, Prem Prasad (Gipan, 2022)
This paper presents various trends, traits and impact of language contact in Maithili language spoken in the Kathmandu valley. The data were gathered through survey and key informant interviews with Maithili speakers and focused-language contact observations in the communities in various parts of the Kathmandu valley. Drawing on such data, this paper reports the expanding instances of language contact among the speakers of Maithili. It also illustrates causes and impacts of language contact in the rapidly emerging multilingual sociolinguistic spaces, especially in the Kathmandu valley. The findings showed that the Maithili native speakers living in Kathmandu had higher instances of language contact with Nepali and English, especially in the formal situations. Such practices were influenced and shaped by their ideological orientations towards globalization and willingness to attend to the emerging diverse contexts caused by the growing migration.